A novel pollen-based method to detect seasonality in ice cores: a case study from the Ortles glacier, South Tyrol, Italy. Issue 229 (2015) - Festi, Daniela; Kofler, Werner; Bucher, Edith; Carturan, Luca; Mair, Volkmar; Gabrielli, Paolo; Oeggl, Klaus
Abstract: We present novel results of pollen analyses performed on a 10 m firn core retrieved from Alto dell'Ortles glacier (3840 m a.s.l.), Eastern Italian Alps, in 2009. The objective was to identify and quantify pollen grains retained in the ice to detect annual and interannual variations in the pollen spectra, thus enabling construction of an accurate pollen-based timescale. Up to now, this has been achieved by pollen diagram interpretation. Here we present a statistical approach developed to extract the seasonal/annual signal contained in the pollen spectra of an ice core. The method is based on principal component analyses of pollen assemblages obtained by high-level taxonomical identification. We apply this approach to the Ortles samples, demonstrating that seasonal and yearly variations of the pollen spectra are easily detectable and provide valuable information that can help improve the chronological model of the firn core. This approach can potentially be used for deeper cores as well as other types of archives (e.g. varved sediments), allowing faster, more objective estimation of yearly and seasonal variations than with classical percentage pollen diagrams.